Causes for the unimodal pattern of biomass and productivity in alpine grasslands along a large altitudinal gradient in semi‐arid regions. (25th June 2012) - Wang, Zhong; Luo, Tianxiang; Li, Ruicheng; Tang, Yanhong; Du, Mingyuan
Abstract: Questions: How can we understand the limitations to plant growth at high altitudes? Our aim was to test the hypotheses that for alpine grasslands along a large altitudinal gradient in semi‐arid regions, plant growth is mainly limited by drought at low altitudes but by low temperature at high altitudes, resulting in a unimodal pattern of biomass and productivity associated with an optimal combination of temperature and precipitation. Such knowledge is important to understanding the response of alpine ecosystems to climate change. Location: We conducted a 5‐yr livestock exclosure experiment along the south‐facing slope of the Nyaiqentanglha Mountains, central Tibetan Plateau. Methods: We measured above‐ and below‐ground biomass, species richness, leaf δ 13 C and water potential, and related climate and soil variables across 42 fenced and unfenced quadrats near seven HOBO weather stations along the slope. The vegetation changed from alpine steppe‐meadow at 4390–4500 m to alpine meadow at 4600–5210 m. Results: Total above‐ and below‐ground biomass across fenced and unfenced quadrats increased with increasing altitude up to 4950–5100 m, and then decreased above 5100 m. Altitudinal trends in leaf δ 13 C and water potential of dominant species also showed a unimodal pattern corresponding to that of vegetation biomass. Total above‐ and below‐ground biomass as well as sedge above‐ground biomass all showed a quadratic relationship with mean temperatures and the ratio of growing season precipitation (GSP) to ≥5 °C accumulated temperature (AccT; R 2 = 0.83−0.88, P < 0.001). In general, above‐ and below‐ground biomass increased with increasing water availability when the GSP/AccT ratio was lower than the threshold level of 0.80–0.84, but decreased when the GSP/AccT ratio was higher than this threshold level. No significant relationship was found between residuals of above‐ground biomass and species richness after removing the effects of climate factors on both stand variables. Conclusions: The results support our hypotheses, further suggesting a threshold of water limitation that is consistent with the model prediction over the Tibetan Plateau. Species richness per se appears to weakly affect community‐level productivity. The response of alpine grasslands to climate warming may vary with altitude because of altitudinal shifts in factors limiting plant growth. Abstract : Above‐ and below‐ground biomass of alpine grasslands along a large altitudinal gradient in central Tibetan Plateau showed a quadratic relationship with the ratio of growing season precipitation to ≥5°C accumulated temperature. This suggests that plant productivity of alpine grasslands in semi‐arid regions is mainly limited by drought at low altitudes but by low temperature at high altitudes.